Assembly and Chiral Memory Effects of Dynamic Macroscopic Supramolecular Helices. Issue 62 (10th September 2018) - Yuan, Tianyu; Sun, Zhimin; Mu, Anthony U.; Zeng, Minxiang; Kalin, Alexander J.; Cheng, Zhengdong; Olson, Mark A.; Fang, Lei
Abstract: Macroscopic enantiomerically pure helical supramolecular fibers are bottom‐up assembled in aqueous media from a chiral π‐electron donor template and an achiral π‐electron acceptor. The helices can be assembled to the sub‐millimeter scale with controlled handedness. These dynamic supramolecular architectures allow for a quantitative exchange of the chiral donor template with achiral analogues. During this process, a chiral memory effect was observed, affording enantiomerically pure helices composed entirely of achiral components. Abstract : Macroscopic enantiomerically pure helical supramolecular fibers were bottom‐up assembled in aqueous media from a chiral π‐electron donor template and an achiral π‐electron acceptor. The helices can be assembled to the sub‐millimeter scale with controlled handedness.